Coating process for blue laser element optical filter

By using a double-polished sapphire substrate and alternately superimposed high and low refractive index material layer coating process on the filters of blue laser components, the problem that traditional coating technology cannot meet the efficiency, stability and reliability requirements of blue lasers is solved. , efficient light reflection and transmission effect is achieved, and the film layer is decomposed at high temperature.

CN119433461AInactive Publication Date: 2025-02-14JIANGXI CRYSTAL OPTECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411496177.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional coating technology cannot meet the efficiency, stability and reliability requirements of blue laser components, and high-temperature blue light laser filters are prone to defiling or cracking when baked at 780°C for 2 hours.

Method used

Using double-pitched sapphire as the substrate, double-sided coating is performed in the coating machine, first plate the first film stack, and then the second film stack is plated, using the alternating superposition structure of the high-refractive index material layer and the low-refractive index material layer, combined with Ion beam bombardment technology forms a stable film layer.

Benefits of technology

It realizes large-angle reflection of light with wavelengths of 580-700nm, and high transmission of blue light bands in the 420-470nm band range, avoids film defiling or film cracking at high temperatures, and improves the performance and reliability of the laser.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433461A_ABST
    Figure CN119433461A_ABST
Patent Text Reader

Abstract

The invention relates to a coating process for an optical filter of a blue laser element. The coating process comprises the following steps: preparing a base material, cleaning and selecting, plating a first film stack, checking parameters, cleaning and selecting for the second time, plating a second film stack, checking parameters for the second time, and finishing the final plating of a short-wave pass optical filter. Compared with the prior art, the high-temperature blue laser filter has the advantages that light with the wavelength of 580-700 nm or above can be reflected, blue light can penetrate through the high-temperature blue laser filter, and under the condition that the high-temperature blue laser filter is baked for 2 h at the temperature of 780 DEG C, the phenomenon of film stripping or film cracking does not occur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating process, in particular to a coating process for a blue laser element filter. Background Art

[0002] In the manufacturing process of blue lasers, component coating is a crucial process. Coating can improve the performance of the laser, optimize its output power and stability, and thus meet the needs of various application scenarios. With the advancement of technology and changes in market demand, the coating process of blue laser components is also constantly developing. However, traditional coating technology cannot meet market demand, and the efficiency, stability and reliability of the laser after coating cannot be guaranteed. In addition, the traditional coating process will cause the high-temperature blue light laser filter to peel off or crack when baked at 780℃ for 2h. Summary of the invention

[0003] The purpose of the present invention is to provide a coating process for a blue laser element filter in order to overcome the defects of the prior art.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A coating process for a blue laser element filter, the coating process comprising the following steps:

[0006] 1) Prepare the substrate: select a 2-inch double-polished sapphire as the filter substrate, use Ta2O5 as the high refractive index material layer, and use SIO2 as the low refractive index material layer;

[0007] 2) Cleaning and selection: The double-polished sapphire substrate is ultrasonically cleaned, then the substrate is dried using a centrifugal dryer, and then the dried substrate is dried again, and finally selected using a dedicated coating fixture on a clean clean bench;

[0008] 3) Plating the first film stack: the selected substrates in 2) are placed in the ball cover of the coating machine from the inside out and evacuated, the substrate temperature is set at 250℃±10℃, and the high refractive index material layer and the low refractive index material layer are pre-melted before coating. The pre-melting time of each layer is 0-40s, and the pre-melting current is 150-450mA. The vacuum is evacuated to 1.0e-3Pa to meet the opening vacuum condition, and then pre-cleaned by the ion source. A baffle is set between the substrate and the ion source and opened. The ion source emits high-frequency ions to bombard the surface during stable operation. High refractive index material layers and low refractive index material layers are alternately superimposed on the upper surface of the substrate. During the deposition process, the ion beam continuously bombards to assist in coating. When the deposition of the film layer stops, the ion source baffle is closed. At this time, a smaller energy ion beam continues to bombard the film layer until the next film layer begins to be deposited. This cycle is repeated until the coating of the first film stack is completed;

[0009] 4) Parameter inspection: Use Olympus reflectance instrument to measure the reflectance spectrum, and use strong light to inspect the appearance of the substrate surface;

[0010] 5) Second cleaning and selection: repeat step 2) to clean and select the substrate after the first film stack is plated;

[0011] 6) Plating the second film stack: repeat step 3) to plate the second film stack on the lower surface of the substrate after the first film stack is plated, and the coating temperature is set at 220°C ± 10°C;

[0012] 7) Second parameter check: Use Shimadzu UV1800 spectrophotometer to test transmittance, and use strong light to check the lower surface of the substrate to complete the short-wave filter plating.

[0013] Further, the structure of the first membrane stack is: G / 1.522L 0.369H 0.5761L 0.775H1.075L0.823H 1.23L / Air; the structure of the second membrane stack is: G / 1.325L 0.918H1.105L 1.521H 1.181L1.241H 1.025L 1.263H 1.026L 1.113H 1.201L1.424H 0.961L 1.012H 1.011L 1.051H10294L 1.068H 1.040L 1.0671H1.260L 1.361H 1.334L 1.238H 1.260L 1.211H 1.360L1.181H 1.160L1.183H 1.160L.0.924H 0.961L 1.198H 1.210L 1.521H 1.181L1.241H1.025L 1.263H 1.026L 1.113H 1.201L 1.424H 0.961L 1.012H 1.011L1.051H10294L 1.068H 1.040L 1.012H 1.549L 1.361H 1.334L 1.278H1.398L / Air;

[0014] Among them, G is a double-polished sapphire substrate, H represents a high-refractive index material layer with an optical thickness of λ / 4, L represents a low-refractive index material layer with an optical thickness of λ / 4, and Air is an air layer.

[0015] Furthermore, the thickness of the high refractive index material layer H is 0.1 μm-0.3 μm; the thickness of the low refractive index material layer L is 0.1 μm-0.4 μm.

[0016] Furthermore, in the above 3), when the substrate is pre-cleaned, the ion source needs to be started 0-60 minutes in advance, the ion source beam acceleration voltage U=0-1500V, and the ion source beam current I=0-1500mA.

[0017] Furthermore, in the coating in 3), electron gun heating evaporation is adopted; the vacuum degree of the high refractive index material layer during coating is 0.4E-2Pa-2.9E-2Pa, the film forming rate is 0.3-0.6nm / s, the thickness is 0.1μm-0.3μm, and the EB2 deflection current is 150-570mA.

[0018] Furthermore, the vacuum degree of the low refractive index material layer in 3) during coating is 0.5E-2Pa-2.7E-2Pa, the film forming rate is 0.4-1.5nm / s, the thickness is 0.1μm-0.4μm, and the EB1 deflection current is 100-300mA.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] The present invention uses double-polished sapphire as a substrate for double-sided coating. After the coating, the short wavepass filter can reflect light with a wavelength of 580-700nm at a large angle, has a high transmittance for blue light in the 420-470nm band, and solves the problem of film peeling or film cracking of high-temperature blue light laser filters when baked at 780°C for 2h. The short wavepass filter can be widely used in blue high-intensity laser components. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of the coating structure provided by the present invention;

[0022] Figure 2 A schematic diagram of the transmittance spectrum of the sapphire substrate provided by the present invention;

[0023] Figure 3 It is a schematic diagram of the reflection spectrum of the first film stack coated on one side of the substrate provided by the present invention;

[0024] Figure 4 It is a schematic diagram of the transmittance spectrum of the substrate with the second film stack coated on one side provided by the present invention;

[0025] Figure 5 It is a schematic diagram of the transmittance spectrum of the finished product provided by the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0027] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example

[0029] like Figure 1 As shown, a coating process for a blue laser element filter, the coating process comprises the following steps:

[0030] 1) Prepare the substrate: select a 2-inch double-polished sapphire as the filter substrate, use Ta2O5 (tantalum pentoxide) as the high refractive index material layer, and use SIO2 (silicon dioxide) as the low refractive index material layer;

[0031] 2) Cleaning and selection: The double-polished sapphire substrate is ultrasonically cleaned, then the substrate is dried using a centrifugal dryer, and then the dried substrate is dried again. Finally, a special coating fixture is used on a clean clean bench to select the substrates, mainly to remove the substrates with bad scratches and marks on the surface;

[0032] 3) Plating the first film stack: Place the selected substrates in 2) into the ball cover of the coating machine from the inside out and evacuate, set the substrate temperature at 250℃±10℃, pre-melt the high refractive index material layer and the low refractive index material layer before coating, the pre-melting time for each layer is 0-40s, the pre-melting current is 150-450mA, and evacuate to 1.0e-3Pa to meet the opening vacuum condition, and then pre-clean through the ion source. A baffle is set between the substrate and the ion source to open. The ion source emits high-frequency ions to bombard the surface during stable operation, and high refractive index material layers and low refractive index material layers are alternately superimposed on the upper surface of the substrate. During the deposition process, the ion beam continuously bombards the auxiliary coating. When the deposition of the film layer stops, the ion source baffle is closed. At this time, a smaller energy ion beam will continue to bombard the film layer until the next film layer Deposition begins, and the cycle is repeated until the coating of the first film stack is completed; when the substrate is pre-cleaned, the ion source must be started 0-60 minutes in advance, the ion source beam acceleration voltage U=0-1500V, the ion source beam current I=0-1500mA, and electron gun heating evaporation is used during coating. The opening vacuum degree of the high refractive index material layer during coating is 0.4E-2Pa-2.9E-2Pa, the film forming rate is 0.3-0.6nm / s, the thickness is 0.1μm-0.3μm, and the EB2 deflection current is 150-570mA; the opening vacuum degree of the low refractive index material layer during coating is 0.5E-2Pa-2.7E-2Pa, the film forming rate is 0.4-1.5nm / s, the thickness is 0.1μm-0.4μm, and the EB1 deflection current is 100-300mA.

[0033] 4) Parameter inspection: Use Olympus reflectance instrument to measure reflectance spectrum, ensure the stability and consistency of spectrum measurement, and inspect the surface appearance of the substrate with a strong light;

[0034] 5) Second cleaning and selection: repeat step 2) to clean and select the substrate after the first film stack is plated;

[0035] 6) Plating the second film stack: repeat step 3) to plate the second film stack on the lower surface of the substrate after the first film stack is plated, and the coating temperature is set at 220°C ± 10°C;

[0036] 7) Second parameter check: Use Shimadzu UV1800 spectrophotometer to test transmittance to ensure the stability and consistency of spectral measurement, and use strong light to check the lower surface of the substrate to complete the plating of short wave pass filter.

[0037] The first film stack of the present invention is deposited on the upper surface of the substrate, and the second film stack is deposited on the lower surface of the substrate, wherein the film system design structure of the first film stack is G|0.5L2HL|^LAir, and the film system design structure of the second film stack is G|0.5LH0.5L|^LAir, wherein G is a double-polished sapphire substrate, H represents a high refractive index material layer with an optical thickness of λ / 4, L represents a low refractive index material layer with an optical thickness of λ / 4, "^" can be an odd number or an even number, and Air is an air layer. The film system design structure is formed by plating high refractive index material layers H and low refractive index material layers L that are alternately overlapped.

[0038] The structure of the first film stack after the final coating is: G / 1.522L 0.369H 0.5761L 0.775H1.075L0.823H 1.23L / Air;

[0039] The structure of the second membrane stack is: G / 1.325L 0.918H 1.105L 1.521H 1.181L 1.241H1.025L1.263H 1.026L 1.113H 1.201L 1.424H 0.961L 1.012H 1.011L1.051H 10294L 1.068H1.040L 1.0671H 1.260L 1.361H 1.334L 1.238H1.260L 1.211H 1.360L 1.181H 1.160L1.183H 1.160L.0.924H 0.961L1.198H 1.210L 1.521H 1.181L 1.241H 1.025L 1.263H1.026L 1.113H1.201L 1.424H 0.961L 1.012H 1.011L 1.051H 10294L 1.068H1.040L1.012H 1.549L 1.361H 1.334L 1.278H 1.398L / Air;

[0040] Among them, G is a double-polished sapphire substrate, H represents a high-refractive index material layer with an optical thickness of λ / 4, L represents a low-refractive index material layer with an optical thickness of λ / 4, and Air is an air layer; the thickness of the high-refractive index material layer H is 0.1μm-0.3μm; the thickness of the low-refractive index material layer L is 0.1μm-0.4μm.

[0041] like Figures 2 to 5As shown, the original filter is transparent to light of all wavelengths. When double-polished sapphire is used as the substrate and the filter is formed by coating with alternating high-refractive index material layers and low-refractive index material layers, it has high reflection at a large angle for wavelengths of 580-700nm and high transmittance for blue light in the 420nm-470nm band. It can be widely used in blue high-intensity laser components, and there will be no film peeling or cracking when the high-temperature blue light laser filter is baked at 780℃ for 2h.

[0042] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A coating process for a blue laser element filter, characterized in that: The coating process comprises the following steps: 1) Prepare the substrate: select a 2-inch double-polished sapphire as the filter substrate, use Ta2O5 as the high refractive index material layer, and use SIO2 as the low refractive index material layer; 2) Cleaning and selection: The double-polished sapphire substrate is ultrasonically cleaned, then the substrate is dried using a centrifugal dryer, and then the dried substrate is dried again, and finally selected using a dedicated coating fixture on a clean clean bench; 3) Plating the first film stack: the selected substrates in 2) are placed in the ball cover of the coating machine from the inside out and evacuated, the substrate temperature is set at 250℃±10℃, and the high refractive index material layer and the low refractive index material layer are pre-melted before coating. The pre-melting time of each layer is 0-40s, and the pre-melting current is 150-450mA. The vacuum is evacuated to 1.0e-3Pa to meet the opening vacuum condition, and then pre-cleaned by the ion source. A baffle is set between the substrate and the ion source and opened. The ion source emits high-frequency ions to bombard the surface during stable operation. High refractive index material layers and low refractive index material layers are alternately superimposed on the upper surface of the substrate. During the deposition process, the ion beam continuously bombards to assist in coating. When the deposition of the film layer stops, the ion source baffle is closed. At this time, a smaller energy ion beam continues to bombard the film layer until the next film layer begins to be deposited. This cycle is repeated until the coating of the first film stack is completed; 4) Parameter inspection: Use Olympus reflectance instrument to measure the reflectance spectrum, and use strong light to inspect the appearance of the substrate surface; 5) Second cleaning and selection: repeat step 2) to clean and select the substrate after the first film stack is plated; 6) Plating the second film stack: repeat step 3) to plate the second film stack on the lower surface of the substrate after the first film stack is plated, and the coating temperature is set at 220°C ± 10°C; 7) Second parameter check: Use Shimadzu UV1800 spectrophotometer to test transmittance, and use strong light to check the lower surface of the substrate to complete the short-wave filter plating.

2. The coating process for a blue laser element filter according to claim 1, characterized in that: The structure of the first membrane stack is: G / 1.522L 0.369H 0.5761L 0.775H 1.075L0.823H 1.23L / Air; the structure of the second membrane stack is: G / 1.325L 0.918H 1.105L1.521H 1.181L 1.241H 1.025L 1.263H1.026L 1.113H 1.201L 1.424H0.961L 1.012H 1.011L 1.051H 10294L 1.068H 1.040L1.0671H 1.260L1.361H 1.334L 1.238H 1.260L 1.211H 1.360L 1.181H 1.160L1.183H1.160L.0.924H 0.961L 1.198H 1.210L 1.521H 1.181L 1.241H 1.025L1.263H1.026L 1.113H 1.201L 1.424H 0.961L 1.012H 1.011L 1.051H10294L 1.068H 1.040L1.012H 1.549L 1.361H 1.334L 1.278H 1.398L / Air; Among them, G is a double-polished sapphire substrate, H represents a high-refractive index material layer with an optical thickness of λ / 4, L represents a low-refractive index material layer with an optical thickness of λ / 4, and Air is an air layer.

3. The coating process for a blue laser element filter according to claim 2, characterized in that: The thickness of the high refractive index material layer H is 0.1 μm-0.3 μm; the thickness of the low refractive index material layer L is 0.1 μm-0.4 μm.

4. The coating process for a blue laser element filter according to claim 1, characterized in that: When the substrate is pre-cleaned in the above 3), the ion source needs to be started 0-60 minutes in advance, the ion source beam acceleration voltage U=0-1500V, and the ion source beam current I=0-1500mA.

5. The coating process for a blue laser element filter according to claim 1, characterized in that: In the coating in 3), electron gun heating evaporation is adopted; the vacuum degree of the high refractive index material layer during coating is 0.4E-2Pa-2.9E-2Pa, the film forming rate is 0.3-0.6nm / s, the thickness is 0.1μm-0.3μm, and the EB2 deflection current is 150-570mA.

6. The coating process for a blue laser element filter according to claim 1, characterized in that: The vacuum degree of the medium and low refractive index material layer during coating is 0.5E-2Pa-2.7E-2Pa, the film forming rate is 0.4-1.5nm / s, the thickness is 0.1μm-0.4μm, and the EB1 deflection current is 100-300mA.

Citation Information

Patent Citations

  • Visible and near infrared wave band slit protection sheet using sapphire as its substrate

    CN106019426A

  • Visible light large-angle incidence and low-reflection infrared cut-off filter and film system design

    CN112147732A

  • Infrared optical filter and production method of the same

    JP2013054368A

  • Blue ray filter element which comprises: a substrate and a hazardous blue ray filtering coating layer combined with one of surfaces of the substrate

    TW201706635A